2009
DOI: 10.1002/jctb.2179
|View full text |Cite
|
Sign up to set email alerts
|

Use of native species and biodegradable chelating agents in the phytoremediation of abandoned mining areas

Abstract: The application of assisted phytoextraction to the remediation of abandoned mining areas can be a valuable method to reclaim these areas without modifying soil and landscape characteristics. An in situ application of continuous phytoextraction technique was carried out in the area of Campo Pisano, near Iglesias (Sardinia, Italy) followed by a laboratory assisted phytoextraction test using the biodegradable chelating agents MGDA and IDS. The plants used were Scrophularia canina L. subsp. bicolor, Cistus salviif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
5
13
1
Order By: Relevance
“…Zinc is the most abundant metal in the bulk soils (24,900 CP -32,700 OCP mg/kg), rhizospheres (26,300 CP -27,300 OCP mg/kg) and in the plant tissues (890 OCP -3290 CP mg/kg), followed by Pb (1240 OCP -5000 CP mg/kg in the soils, 1600 OCP -5030 CP mg/kg in the rhizospheres, and 50 OCP -1020 CP mg/kg in the plant tissues) and Cd (100 CP -340 OCP mg/kg in the soils, 170 CP -280 OCP mg/kg in the rhizospheres, and 13 OCP -31 OCP mg/kg in the plant tissues). It should be noted that metal contents detected in this work are of the same order of magnitude as in previous studies [39,41,46,91], in which relevant local variations due to heterogeneities of the mine tailings can be highlighted. [92] 1208 954 BCF, BAC, and TF (Table 3) were calculated to investigate the transfer of metals from geosphere to plant tissues and their translocation from the roots to the epigean organs.…”
Section: Discussionsupporting
confidence: 81%
“…Zinc is the most abundant metal in the bulk soils (24,900 CP -32,700 OCP mg/kg), rhizospheres (26,300 CP -27,300 OCP mg/kg) and in the plant tissues (890 OCP -3290 CP mg/kg), followed by Pb (1240 OCP -5000 CP mg/kg in the soils, 1600 OCP -5030 CP mg/kg in the rhizospheres, and 50 OCP -1020 CP mg/kg in the plant tissues) and Cd (100 CP -340 OCP mg/kg in the soils, 170 CP -280 OCP mg/kg in the rhizospheres, and 13 OCP -31 OCP mg/kg in the plant tissues). It should be noted that metal contents detected in this work are of the same order of magnitude as in previous studies [39,41,46,91], in which relevant local variations due to heterogeneities of the mine tailings can be highlighted. [92] 1208 954 BCF, BAC, and TF (Table 3) were calculated to investigate the transfer of metals from geosphere to plant tissues and their translocation from the roots to the epigean organs.…”
Section: Discussionsupporting
confidence: 81%
“…The concentrations of lead in the aerial part from São Domingos plants were in the same range than those reported for leaves and twigs (10.7 and 17.9 mg/kg, respectively) in other areas from the same mine (Freitas et al, 2004a). However, Cao et al (2009), in Campo Pisano mine, reported lead concentrations up to 185 mg/kg in the aerial parts of the same plant species growing in tailings with greater available lead fraction than that obtained in Caveira mine area. As expected, plants growing in the non-contaminated soils presented the smallest lead concentrations (0.95 ± 0.22 and 3.53 ± 0.84 mg/kg for aerial parts and roots, respectively).…”
Section: Leadsupporting
confidence: 58%
“…The obtained results for zinc in the C. salviifolius aerial parts from São Domingos are in the same range of concentrations in leaves (226.2 mg/kg) and twigs (130.4 mg/kg) for the same species, reported by Freitas et al (2004a) for São Domingos mine areas where soils contain smallest zinc concentration (158.9 mg/kg). However, in tailings from Campo Pisano mine with large total and available zinc concentrations in soils (12038 and 3504 mg/kg, respectively), the same species concentrate in the aerial part 1560 mg Zn/kg which is approximately 9-fold more than that of plants from Caveira and São Domingos (Cao et al, 2009). Large zinc concentrations in soil, both total and available fraction, seem to play an important role in this chemical element absorption and translocation to the aboveground part of C. salviifolius as was also observed for the studied mine areas.…”
Section: Antimonymentioning
confidence: 96%
“…A more widely applicable technique is phytostabilization, because the quick establishment of a dense vegetation cover is crucial to limit wind and water erosion. Moreover, plant roots may immobilize metals by adsorption or accumulation, and provide a rhizosphere wherein metals precipitate and stabilize (Mendez & Maier 2008;Cao et al, 2009;Nicoară et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%